Dispersion method of lithium battery negative electrode slurry
Through reasonable raw material addition sequence and stirring method, combined with electrostatic interaction dispersant, the problems of low production efficiency and poor dispersion in the preparation process of lithium battery negative electrode slurry are solved, and efficient and stable slurry dispersion is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202510001812.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium battery negative electrode slurry preparation process has problems such as low production efficiency and poor slurry dispersion, which leads to long process time and high cost, making it difficult to meet the needs of industrial production.
By setting a reasonable order of raw material addition and stirring method, the dispersant N,N'-dimethyl-4,4'-bipyridine hexafluorophosphate is added, and the negative electrode main material is effectively dispersed by electrostatic interaction, thereby enhancing the dispersion of the slurry.
On the premise of ensuring the stability of the slurry viscosity, the dispersion of the negative electrode slurry is significantly improved, the process flow is simplified, the production efficiency is improved, and it is suitable for industrial applications.
Smart Images

Figure CN119812323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery homogenization technology, and specifically relates to a method for dispersing negative electrode slurry of a lithium battery. Background Art
[0002] Lithium-ion secondary batteries have become widely used power products due to their advantages such as high single-cell voltage, high energy density, long cycle life, low self-discharge rate, no memory effect, and no pollution. Their application areas mainly include new energy vehicles, power tools, electric bicycles; various portable electronic consumer products (such as laptops, tablets, smart phones, digital cameras, etc.); home energy storage, commercial and industrial energy storage, grid-level energy storage, etc.; especially in recent years, with the application in electric vehicles and energy storage batteries, people have put forward higher performance requirements for lithium-ion batteries. The improvement of lithium-ion battery performance is not only limited by the performance of various battery materials (such as positive electrode materials, negative electrode materials, electrolytes, and diaphragms), but also affected by the preparation process of lithium-ion batteries. Among them, the homogenization process is the first process and the most core process. The performance of the slurry directly determines the performance of the battery.
[0003] The preparation of negative electrode slurry for lithium-ion batteries is mainly divided into two preparation methods: dry method and wet method. The choice of slurrying process can directly affect the dispersibility of slurry, and has a direct impact on the production, performance and electrochemical performance of electrode sheets. Wet slurrying of negative electrode has the disadvantages of low production efficiency and poor slurry dispersibility. The slurrying process steps are as follows: first, the thickener and the conductive agent are mixed evenly, and then the negative electrode main material, solvent, binder, etc. are added and stirred and dispersed. In this process, the conductive agent absorbs the solvent, which makes the subsequent negative electrode main material easy to agglomerate, resulting in increased slurry viscosity and uneven slurry dispersion. Therefore, the slurry dispersibility is improved by extending the stirring time or adding a dispersant, which greatly reduces the production efficiency and increases the production cost.
[0004] In the existing negative electrode slurry preparation process, it is often necessary to extend the homogenization time to achieve better dispersion of the slurry. At present, the negative electrode slurry preparation time generally used by lithium battery manufacturers is more than 8 hours. CN102637847B discloses a method of achieving uniform dispersion of the slurry by wave stirring homogenization, but this method still has the disadvantages of long process time and poor compatibility with actual production, which is not conducive to large-scale promotion and application in actual production.
[0005] Therefore, how to improve the dispersibility of negative electrode slurry while ensuring high production efficiency and solve the problems of long process time and low production efficiency in existing technologies has become the focus of research in the industry. Summary of the invention
[0006] The object of the present invention is to provide a method for dispersing negative electrode slurry of a lithium battery, by setting a reasonable raw material addition sequence and stirring method, the slurry has high stability and the dispersant can be evenly distributed, and by adding the dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate, an electrostatic interaction is formed with a negatively charged negative electrode main material, the negative electrode main material is effectively dispersed, and the dispersion performance is further improved under the premise of maintaining the stability of the slurry viscosity.
[0007] In order to achieve the above invention object, the technical solution of the present invention is as follows:
[0008] A method for dispersing a lithium battery negative electrode slurry comprises the following steps:
[0009] (1) Add the negative electrode main material, conductive agent, thickener and dispersant into a homogenizer and stir them, stirring them quickly and slowly at the same time to make the powders mix evenly;
[0010] (2) adding some water to the mixed powder obtained in step (1) and stirring the mixture at a slow speed to initially wet the mixed dry powder;
[0011] (3) After step (2), add a binder and continue to stir slowly to mix the binder evenly, so that the material is in a good slurry state, stir and disperse it fully, and obtain a kneaded slurry after stirring;
[0012] (4) After step (3), the material is scraped and the remaining water is added while simultaneously performing rapid and slow stirring, cooling, and finally obtaining the final negative electrode slurry by vacuuming and sieving.
[0013] In step (1), the stirring speed of slow stirring is 30-70 rpm, the stirring speed of fast stirring is 500-1000 rpm, and the stirring time is 5-20 min.
[0014] Preferably, the main stirring paddle of the homogenizer performs slow stirring, and the auxiliary stirring paddle performs fast stirring.
[0015] In step (2), the stirring speed is 30 to 70 rpm, the stirring time is 5 to 20 min, and based on the total mass of the partial water added in step (2) and the remaining water added in step (4) as 100%, the amount of the partial water added in step (2) is 15 to 40%.
[0016] In step (3), the stirring speed is 30 to 70 rpm, the stirring time is 40 to 60 min, and all the binder is added.
[0017] In step (4), the stirring speed of slow stirring is 30-70 rpm, the stirring speed of fast stirring is 2000-3000 rpm, the stirring time is 40-60 min, and the total mass of the part of water added in step (2) and the remaining water added in step (4) is 100%, and the amount of water added in step (4) is 60-85%.
[0018] Preferably, the dispersant is N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate.
[0019] Preferably, the negative electrode main material is one or more of natural graphite, artificial graphite, mesophase carbon microspheres, silicon / carbon composite materials, tin / carbon composite materials, hard carbon, and lithium carbonate;
[0020] Preferably, the conductive agent is one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube or graphene;
[0021] Preferably, the thickener is sodium carboxymethyl cellulose (CMC);
[0022] Preferably, the binder is one or more of polyvinylidene fluoride (PVDF), styrene butadiene latex (SBR), polyacrylonitrile (PAN) or polyacrylic acid (PAA);
[0023] Preferably, the mass ratio of the negative electrode main material, the conductive agent, the thickener, and the binder is 96-97.8:0.5-1.5:0.4-1.5:1.5-3.0, and the total mass of the negative electrode main material, the conductive agent, the thickener, and the binder is 100%, and the added amount of the dispersant is 0.5-3%;
[0024] Preferably, the solid content of the negative electrode slurry is 45%-55%.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] Compared with the prior art in which a large amount of water is added after the negative electrode main material, conductive agent and thickener are dry-mixed, a binder is kneaded, and then water is added to disperse and make slurry, the present invention adds the dispersant N,N′-dimethyl-4,4′-bipyridyl hexafluorophosphate in the first step. Under the premise of ensuring the viscosity of the slurry, the graphite is effectively dispersed through electrostatic interaction, and the dispersibility of the slurry is greatly improved under the premise of maintaining the stability of the slurry viscosity.
[0027] The negative electrode homogenization process of the present invention is simple to operate, has high production efficiency, and is suitable for actual industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate 1H NMR spectrum
[0029] Figure 2 It is a comparison chart of the slurry fineness of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the related listed items. The top, bottom, etc. mentioned or may be mentioned in this specification are defined relative to the structures shown in the drawings. They are relative concepts and may therefore change accordingly according to their different locations and different usage states.
[0032] Source of raw materials:
[0033] Synthesis of N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate:
[0034] Weigh the white solid 4,4'-bipyridine (7.8g, 50mmol), transfer it to a 250mL round-bottom flask, add a stirring magnet, then add 100mL acetone, after the solid is completely dissolved, add 8.4mL iodomethane (CH3I) colorless liquid, reflux at 60℃ for 2 hours, after the reaction is completed, rotary evaporate, vacuum dry to obtain a solid (product 1). Transfer product 1 to a screw-capped bottle, add 10mL water, after the solid is completely dissolved, weigh NH4PF6 (7.20g, 44mmol) and transfer it to a screw-capped bottle, ultrasonicate for 30 minutes to generate a solid, filter, rinse with water, vacuum dry to obtain the final product N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate.
[0035] 1 H NMR spectrum Figure 1 Test conditions: The spectrometer was Bruker DRX (600 MHz), the sample was dissolved in deuterated DMSO (CD3COCD3, DMSO-d6), and tetramethylsilane (TMS) was used as the internal standard.
[0036] Example 1
[0037] Negative electrode formula: 96.7 parts by mass of graphite QC-8, 1 part by mass of conductive carbon black SP, 0.5 parts by mass of CMC, 1.8 parts by mass of PAA, 3.0 parts by mass of dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate
[0038] A method for dispersing negative electrode slurry of a lithium ion battery comprises the following steps:
[0039] (1) Graphite QC-8, conductive carbon black SP, and CMC were added to a homogenizer at a ratio of 96.7:1:0.5, and 3.0% of the mass of the solid component of the slurry was added as a dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate. The main stirring blade was rotated at a low speed of 50 rpm and the auxiliary stirring blade was rotated at a high speed of 800 rpm for 10 minutes to mix uniformly to obtain a mixture;
[0040] (2) adding 25% of the total amount of deionized water to the mixture of step (1), stirring at a low speed of 50 rpm for 10 min with a main stirring paddle to initially wet the mixed dry powder;
[0041] (3) adding all the binder to the solid particles in step (2), stirring at a low speed of 50 rpm with a main stirring paddle for 50 min to mix the binder evenly so that the slurry reaches a suitable kneading state;
[0042] (4) Scrape the material and add the remaining deionized water to the slurry obtained in step (3). Stir at a low speed of 50 rpm with the main stirring paddle and at a high speed of 2500 rpm with the auxiliary stirring paddle for 50 min. Turn on the circulating cooling water and obtain the final negative electrode slurry by vacuuming and sieving.
[0043] Example 2
[0044] Negative electrode formula: 96.0 parts by mass of graphite FSN-1, 1.2 parts by mass of conductive carbon black SP, 1 part by mass of CMC, 1.8 parts by mass of PAA, 2.0 parts by mass of dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate
[0045] A method for improving the dispersibility of a negative electrode slurry for a lithium ion battery comprises the following steps:
[0046] (1) Graphite FSN-1, conductive carbon black SP, and CMC were added to a homogenizer at a ratio of 96.0:1.2:1, and 2.0% of the mass of the solid component of the slurry was added as a dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate. The main stirring paddle was stirred at a low speed of 35 rpm and the auxiliary stirring paddle was dispersed at a high speed of 600 rpm for 18 minutes to mix uniformly to obtain a mixture;
[0047] (2) adding 30% of the total amount of deionized water to the mixture of step (1), stirring at a low speed of 40 rpm for 15 min to initially wet the mixed dry powder;
[0048] (3) adding all the binder to the solid particles in step (2), stirring at a low speed of 50 rpm with a main stirring paddle for 60 min to mix the binder evenly so that the slurry reaches a suitable kneading state;
[0049] (4) Scraping the material, adding the remaining deionized water to the slurry obtained in step (3), stirring at a low speed of 60 rpm with the main stirring paddle, and dispersing at a high speed of 2900 rpm with the auxiliary stirring paddle for 60 min, turning on the circulating cooling water, and obtaining the final negative electrode slurry by vacuuming and sieving.
[0050] Example 3
[0051] Negative electrode formula: 97.5 parts by mass of graphite QCG-X, 0.6 parts by mass of conductive carbon black SP, 0.4 parts by mass of CMC, 1.5 parts by mass of PAA, 1.0 parts by mass of dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate
[0052] A method for improving the dispersibility of a negative electrode slurry for a lithium ion battery comprises the following steps:
[0053] (1) Graphite QCG-X, conductive carbon black SP, and CMC were added to a homogenizer at a ratio of 97.5:0.6:0.4, and 1.0% of the mass of the solid component of the slurry was added as a dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate. The main stirring paddle was stirred at a low speed of 70 rpm, and the auxiliary stirring paddle was dispersed at a high speed of 1000 rpm for 5 minutes to mix uniformly to obtain a mixture;
[0054] (2) adding 15% of the total amount of deionized water to the mixture of step (1), stirring at a low speed of 60 rpm for 6 minutes with a main stirring paddle to initially wet the mixed dry powder;
[0055] (3) adding all the binder to the solid particles in step (2), stirring at a low speed of 60 rpm with a main stirring paddle for 40 min to mix the binder evenly, so that the slurry reaches a suitable kneading state;
[0056] (4) Scrape the material and add the remaining deionized water to the slurry obtained in step (3). Stir at a low speed of 50 rpm with the main stirring paddle and at a high speed of 2500 rpm with the auxiliary stirring paddle for 50 min. Turn on the circulating cooling water and obtain the final negative electrode slurry by vacuuming and sieving.
[0057] Example 4
[0058] Negative electrode formula: 96.7 parts by mass of graphite HRG-3Y, 1 part by mass of conductive carbon black SP, 0.5 parts by mass of CMC, 1.8 parts by mass of PAA, 0.5 parts by mass of dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate
[0059] A method for improving the dispersibility of a negative electrode slurry for a lithium ion battery comprises the following steps:
[0060] (1) Graphite HRG-3Y, conductive carbon black SP, and CMC were added to a homogenizer at a ratio of 96.7:1:0.5, and 0.5% of the mass of the solid component of the slurry was added as a dispersant N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate. The main stirring paddle was stirred at a low speed of 50 rpm and the auxiliary stirring paddle was dispersed at a high speed of 700 rpm for 10 minutes to mix uniformly to obtain a mixture;
[0061] (2) adding 35% of the total amount of deionized water to the mixture of step (1), stirring at a low speed of 50 rpm with a main stirring paddle for 10 min to initially wet the mixed dry powder;
[0062] (3) adding all the binder to the solid particles in step (2), stirring at a low speed of 50 rpm with a main stirring paddle for 50 min to mix the binder evenly so that the slurry reaches a suitable kneading state;
[0063] (4) Scraping, adding the remaining deionized water to the slurry obtained in step (3), stirring at a low speed of 40 rpm (can be adjusted to 30 rpm, 70 rpm, wherein 50 rpm is used as a preferred embodiment for explanation) with the main stirring paddle, and high-speed dispersion of 2200 rpm with the auxiliary stirring paddle for 60 min, turning on the circulating cooling water, and obtaining the final negative electrode slurry by vacuuming and sieving.
[0064] Comparative Example 1
[0065] The negative electrode slurry was dispersed in the same manner as in Example 1, the main difference being that the selected dispersant was acrylic polyester.
[0066] The five types of lithium battery negative electrode slurries prepared above are evenly coated on the copper foil current collector after adjusting the viscosity by adding water, and the negative electrode sheets are obtained after drying and rolling. The obtained negative electrode sheets can be assembled into lithium-ion batteries. The raw materials, proportions and drying and rolling parameters used in the embodiments and comparative examples are the same. The physical properties of the obtained slurries and the bonding strength of the corresponding electrodes are tested, as shown in the figure below.
[0067] According to the actual coating effect, the five slurries all met the normal coating requirements after adding water to adjust the viscosity, without obvious poor appearance (black spots, scratches, etc.). From the test results in Table 1, it can be seen that the fineness of the negative electrode slurry of Example 1 of the present invention is smaller than that of the comparative example, the slurry filtration time of Example 1 is significantly shorter than that of the comparative example, and the D50 of Example 1 is smaller than the D50 of the comparative example.
[0068] Figure 2 This is a comparison chart of five kinds of pulp fineness. Figure 2 It can be seen that the comparative example has obvious particles under light, while Examples 1, 2, 3, and 4 are relatively fine, indicating that the dispersion effect of the comparative example is poor, or the dispersion time is still insufficient.
[0069] Table 1 shows the performance of lithium battery negative electrode slurry and electrode after viscosity adjustment
[0070] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Homogenization time / min 140 140 140 140 140 Solid content / % 51.56 50.33 49.65 50.74 48.32 Viscosity / cp 4250 4230 4180 4230 4320 Fineness 21 22 23 24 26 Sieving time (400g) / s 186 207 236 355 510 Slurry particle size D50 12.98 13.31 13.55 13.89 14.21 Pole piece bonding force / N / m 17.27 17.68 16.80 17.33 17.03
[0071] In summary, it can be seen that the negative electrode homogenization process of the present invention improves the dispersibility of the slurry while ensuring the stability of the slurry by adding the dispersant N,N′-dimethyl-4,4′-bipyridyl hexafluorophosphate and adjusting the amount of the dispersant added, thereby ensuring the subsequent coating conditions and the bonding strength of the obtained electrode.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for dispersing a negative electrode slurry for a lithium battery, characterized in that: The following steps are involved: (1) Add the negative electrode main material, conductive agent, thickener and dispersant into a homogenizer and stir, and stir quickly and slowly to mix the powders evenly; (2) adding some water to the mixed powder obtained in step (1) and stirring the mixture at a slow speed to initially wet the mixed dry powder; (3) After step (2), add a binder, continue to stir slowly, mix it evenly with the binder, stir and disperse it thoroughly, and obtain a kneaded slurry after stirring; (4) After step (3), the material is scraped and the remaining water is added while simultaneously performing rapid and slow stirring and cooling to obtain a negative electrode slurry.
2. The dispersion method according to claim 1, characterized in that In step (1), the stirring speed of slow stirring is 30 to 70 rpm, the stirring speed of fast stirring is 500 to 1000 rpm, and the stirring time is 5 to 20 min; Preferably, the main stirring paddle of the homogenizer performs slow stirring, and the auxiliary stirring paddle performs fast stirring.
3. The dispersion method according to claim 1 or 2, characterized in that In step (2), the stirring speed is 30 to 70 rpm and the stirring time is 5 to 20 min; Preferably, based on the total mass of the partial water added in step (2) and the remaining water added in step (4) being 100%, the amount of the partial water added in step (2) is 15-40%.
4. The dispersion method according to any one of claims 1 to 3, characterized in that In step (3), the stirring speed is 30 to 70 rpm and the stirring time is 40 to 60 min.
5. The dispersion method according to any one of claims 1 to 4, characterized in that: In step (4), the stirring speed of slow stirring is 30-70 rpm, the stirring speed of fast stirring is 2000-3000 rpm, and the stirring time is 40-60 min; Preferably, based on the total mass of the partial water added in step (2) and the remaining water added in step (4) being 100%, the amount of water added in step (4) is 60 to 85%.
6. The dispersion method according to any one of claims 1 to 5, characterized in that The dispersant is N,N'-dimethyl-4,4'-bipyridyl hexafluorophosphate; Preferably, the negative electrode main material is one or more of natural graphite, artificial graphite, mesophase carbon microspheres, silicon / carbon composite materials, tin / carbon composite materials, hard carbon, and lithium carbonate; Preferably, the conductive agent is one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube or graphene; Preferably, the thickener is sodium carboxymethyl cellulose; Preferably, the binder is one or more of polyvinylidene fluoride, styrene-butadiene latex, polyacrylonitrile or polyacrylic acid.
7. The dispersion method according to any one of claims 1 to 6, characterized in that: The mass ratio of the negative electrode main material, the conductive agent, the thickener, and the binder is 96-97.8:0.5-1.5:0.4-1.5:1.5-3.0; Preferably, the amount of the dispersant added is 0.5-3%, based on the total mass of the negative electrode main material, the conductive agent, the thickener and the binder being 100%; Preferably, the solid content of the negative electrode slurry is 45%-55%.
Citation Information
Patent Citations
Method for preparing high-dispersity lithium battery anode and cathode slurry
CN102637847B
Cited By
Suspension stabilizer as well as preparation method and application thereof
CN121054698A